Identification and differential expression of microRNAs in the ovaries of pigs (Sus scrofa) with high and low litter sizes. (20th July 2016) - Huang, L.; Yin, Z. J.; Feng, Y. F.; Zhang, X. D.; Wu, T.; Ding, Y. Y.; Ye, P. F.; Fu, K.; Zhang, M. Q.
Summary: Litter size affects profitability in the swine industry. Mammalian ovaries play important roles during reproduction, including ovulation and hormone secretion, which are tightly regulated by specific microRNAs (miRNAs). In this study, we investigated the effects of specific miRNAs on porcine litter size. We compared the ovarian miRNAs of Yorkshire pigs with high (YH) and low (YL) litter sizes using Solexa sequencing technology. We identified 327 and 320 miRNAs in the ovaries of YH and YL pigs respectively. A total of 297 miRNAs were co‐expressed; 30 and 23 miRNAs respectively were specifically expressed in the two libraries. A total of 83 novel miRNAs were predicted; 37 specific miRNAs were obtained, of which 21 miRNAs were upregulated and 16 miRNAs were downregulated in YH compared with YL. Additionally, 19 628 and 19 250 target genes were predicted in the two libraries respectively. The results revealed that specific miRNAs (i.e., miR‐224, miR‐99a, let‐7c, miR‐181c, miR‐214 and miR‐21) may affect porcine litter size. The results of this study will help in gaining understanding of the role of miRNAs in porcine litter size regulation.